Koorlangka Dreaming Becomes a Reality: A Moombaki Virtual Reality with Connections to Noongar Moort, Boodja, and Karnarn - Cheryl S. Kickett-Tucker; Jennifer Dodd; Deborah Johnson; Donna Cross (Genealogy, 2025)
In this paper, we describe the developmental process of a culturally grounded Moombaki virtual reality (VR) game. We share how Aboriginal children’s drawings have informed the creation of an interactive learning platform for primary school-aged children attending schools in Wadjuk Boodja. The project focused on connecting students to cultural knowledge through immersive storytelling, creative exploration, and collaborative design by using small group yarning circles and game development activities. The aim of the yarning sessions was to identify, explore, and understand the knowledge Aboriginal children had of Aboriginal identity and culture, including protocols, ceremonies, stories, Dreamtime, languages, and traditional practices, and how best to represent these concepts in the cultural learning journey using virtual reality.